Nitration of Wheat Amylase Trypsin Inhibitors Increases Their Innate and Adaptive Immunostimulatory Potential in vitro - Ziegler, Kira; Neumann, Jan; Liu, Fobang; Fröhlich-Nowoisky, Janine; Cremer, Christoph; Saloga, Joachim; Reinmuth-Selzle, Kathrin; Pöschl, Ulrich; Schuppan, Detlef; Bellinghausen, Iris; Lucas, Kurt (Frontiers in Immunology, 2019)
Amylase trypsin inhibitors (ATI) can be found in all gluten containing cereals and are, therefore, ingredient of basic foods like bread or pasta. In the gut ATI can mediate innate immunity via activation of the Toll-like receptor 4 (TLR4) on immune cells residing in the lamina propria, promoting intestinal, as well as extra-intestinal, inflammation. Inflammatory conditions can induce formation of peroxynitrite (ONOO-) and, thereby, endogenous protein nitration in the body. Moreover, air pollutants like ozone (O3) and nitrogen dioxide (NO2) can cause exogenous protein nitration in the environment. Both reaction pathways may lead to the nitration of ATI. To investigate if and how nitration modulates the immunostimulatory properties of ATI, they were chemically modified by three different methods simulating endogenous and exogenous protein nitration and tested in vitro. Here we show that ATI nitration was achieved by all three methods and lead to increased immune reactions. We found that ATI nitrated by tetranitromethane (TNM) or ONOO- lead to a significantly enhanced TLR4 activation. Furthermore, in human primary immune cells, TNM nitrated ATI induced a significantly higher T cell proliferation and release of Th1 and Th2 cytokines compared to unmodified ATI. Our findings implicate a causative chain between nitration, enhanced TLR4 stimulation, and adaptive immune responses, providing major implications for public health, as nitrated ATI may strongly promote inhalative wheat allergies (baker’s asthma), non-celiac wheat sensitivity (NCWS), other allergies, and autoimmune diseases. This underlines the importance of future work analyzing the relationship between endo- and exogenous protein nitration, and the rise in incidence of ATI-related and other food hypersensitivities.